The Effect Of Cafed Attempt and Prices on Customer Satisfaction Coffee Shop Source Coffee Sidoarjo - Erlina Dian Titania Jannah; Renny Dwijayanti (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine the effect of cafe atmosphere and price on customer satisfaction at Source Coffee Sidoarjo. The following type of research is quantitative research and the sampling technique used is purposive sampling. The research sample used is the number of 100 respondents. Data analysis techniques using descriptive statistics, data analysis used is multiple linear regression with SPSS version 25. Results obtained from this study indicate that the cafe atmosphere variables (X1) a significant influence on customer satisfaction (Y), while in the variable price (X2) are also significantly affect customer satisfaction (Y) and the cafe atmosphere variables (X1) and price (X2) simultaneously have a significant influence on customer satisfaction (Y) in Source Coffee Sidoarjo